Atherosclerosis and arterial stiffness in obstructive sleep apnea--a cardiovascular magnetic resonance study. - Kylintireas, I; Craig, S; Nethononda, R; Kohler, M; Francis, J; Choudhury, R; Stradling, J; Neubauer, S (2012)
OBJECTIVE: Obstructive sleep apnoea (OSA) has been linked to cardiovascular risk factors, such as hypertension, and clinical cardiovascular endpoints. Our aim was to assess whether OSA is independently associated with atherosclerosis and vascular dysfunction as assessed by cardiovascular magnetic resonance (CMR). METHODS: 58 patients with OSA and 39 matched control subjects without OSA underwent CMR of the aorta and carotid arteries. Carotid and aortic wall thickness and aortic distensibility were measured. Multi-weighted, high resolution CMR imaging was used for carotid atheroma characterization according to the American Heart Association (AHA) atheroma classification, modified for CMR. RESULTS: Carotid [1.47±0.03 mm vs. 1.26±0.05 mm, (P<0.01)] and aortic wall thickness [2.95±0.09 mm vs. 2.05±0.07 mm, (P<0.001)] were increased in patients with OSA compared to controls. Aortic distensibility was decreased in patients with OSA [3.62±0.3 vs. 4.75±0.2 mmHg(-1)×10(-3), (P<0.05)]. Prevalence of carotid plaque, average carotid atheroma class, and prevalence of high risk features of carotid atheroma were increased in patients with OSA (P<0.005 for all). On multivariate analysis, Oxygen desaturation index (ODI) emerged as an independent predictor of carotid and aortic wall thickness, but not of aortic stiffness. CONCLUSIONS: OSA is associated with increased carotid and aortic atheroma burden and with advanced, high risk carotid atherosclerotic plaques, but not with aortic stiffening.